Thermal, mechanical, and electrical properties of rubber latex with TiO2 nanoparticles. (December 2020) - Naphon, P.; Wiriyasart, S.; Naphon, N.
Abstract: Due to the accumulation of the generated heat, the electrical wire insulator is melt and causes the fire. To decrease the accumulated heat, therefore, the heat transfer enhancement from the electrical wire insulator can be achieved by increasing the thermal conductivity of the electrical wire insulator. However, the electrical resistivity and mechanical properties are optimized too. In this study, the effects of nanoparticles content of 0, 0.1–1.0, 10, and 20 phr on the thermal, electrical, and mechanical properties of the natural rubber are presented. It can be found that the TiO2 nanoparticles have a significant effect on the increasing thermal conductivity while the electrical resistivity tends to decrease with increasing nanoparticle content. However, the tensile stress of the rubber compound tends to increase. The results obtained from this study disclose different properties that influence the strength, thermal and electrical resistance of latex rubber based composites reinforced by surface unmodified and modified nanoparticles, which is helpful not only for the understanding of performance of nanoparticle-reinforced flexible elastomer composites, but also for the design of novel flexible composites with matching strength and thermal and electrical resistance. Highlights: Due to the accumulation of the generated heat, the electrical wire insulator is melt and caused of fire. In order to decrease the accumulated heat, therefore, the heat transfer enhancement from the electrical wire insulator can be achieved by increasing thermal conductivity of the electrical wire insulator. However, the electrical resistivity and mechanical properties are also optimized too. The results obtained from this study disclose different properties that influence the strength, thermal and electrical resistance of latex rubber based composites reinforced by surface unmodified and modified nanoparticles.